Pengaruh Gaya Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja pada Pegawai Dinas Pariwisata Kabupaten Kolaka Utara - Patehuddin; Congge, Umar; A. Djamaluddin (The Journal Publishing, 2025)
This study aims to determine the influence of leadership style, motivation and work discipline on employee performance at the North Kolaka Regency Tourism Office. This research was held at the North Kolaka Regency Tourism Office. The sample in this study is all employees totaling 32 people. This study is a quantitative research with a data analysis method using multiple linear regression. The results of this study show that (1) The validation test on the variables Leadership Style (GK), Motivation (M), and Work Discipline (DK) meets the criteria for excellent validity. The results of the significance test (Sig 2-Tailed) which is smaller than 0.05 and the Pearson Correlation value greater than the r-table value (0.339) show that each statement item has a significant relationship with the variables measured, so that the instruments used in this study are reliable and feasible to be used for further research. (2) Reliability tests conducted using Cronbach's Alpha showed excellent results for all the variables tested. The Cronbach's Alpha values obtained for the variables Leadership Style (0.856), Motivation (0.947), Work Discipline (0.956), and Performance (0.820) were all greater than 0.60, which indicates that the questionnaire instrument used in this study is reliable. This means that each question item in the questionnaire is able to provide consistent and repeatable results to obtain similar data if resubmitted. (3) The normality test using the Kolmogorov-Smirnov test, obtained an Adjusted R Square of 0.820 or 82%. This shows that the variables Leadership Style, Motivation, and Work Discipline have a significant influence on employee performance at the North Kolaka Regency Tourism Office by 82%.